Synthesis and Characterization of TiN‐coated Cubic Boron Nitride Powders. Issue 5 (11th October 2013) - Chen, Deliang; Liu, Zhongsheng; Fan, Bingbing; Li, Jian; Cao, Wenbo; Wang, Hailong; Lu, Hongxia; Xu, Hongliang; Zhang, Rui
<x xml:space="preserve">Abstract</x> Titanium nitride‐coated cubic boron nitride (TiN/cBN) composite powders were prepared by nitridizing TiO2/cBN powders in a NH3 flow at 950°C. The TiO2/cBN powders were synthesized via a sol‐gel process using tetra‐butyl titanate and concentrated‐HNO3‐treated BN powders as starting materials. The techniques of XRD, SEM, TEM, FT‐IR, and TG‐DTA were used to characterize the products and their intermediates. The cBN powders were uniformly coated with TiN nanoparticles. During the nitridization, the morphology of the TiO2/cBN powders is unchanged. The TiN/cBN powders can be used as starting materials to prepare polycrystalline cBN compacts, or as reinforcements to strengthen metal‐matrix composites.